2004
DOI: 10.1002/ana.20358
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin‐1β contributes to the generation of experimental febrile seizures

Abstract: Fever can provoke "febrile" seizures (FS). Because complex FS may promote development of temporal lobe epilepsy, understanding their mechanisms is clinically important. Using an immature rodent model and transgenic technology, we examined the role of interleukin-1beta, (IL-1beta), a pyrogenic, proinflammatory cytokine, in FS. IL-1beta receptor-deficient mice were resistant to experimental FS. This resistance appeared independent of genetic background and was attributed to lack of IL-1beta signaling, because ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
315
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 396 publications
(343 citation statements)
references
References 20 publications
16
315
1
5
Order By: Relevance
“…Early-life inflammatory factors such as IL-1β have been associated with FS generation and seizure susceptibility in the adult brain [19] . It has been reported that IL-1β increases seizure susceptibility to kainic acid in adult rodents [33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early-life inflammatory factors such as IL-1β have been associated with FS generation and seizure susceptibility in the adult brain [19] . It has been reported that IL-1β increases seizure susceptibility to kainic acid in adult rodents [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Baseline hippocampal electroencephalograms (EEGs) were recorded 24 h later, followed by seizure induction by hyperthermia and MES [18,19] . In detail, electrodes were implanted under halothane anesthesia (2%-3% halothane inhaled through muzzle), using an infant rat stereotaxic apparatus (512600, Stoelting).…”
Section: Electrophysiological Recording In Vivomentioning
confidence: 99%
“…Experimental seizures in rodents induce inflammatory processes in brain regions in which epileptic activity originates and spreads [1,2]; in this respect, the activation of the interleukin (IL)-1β/IL-1 receptor type 1 (R1) signaling in glia and neurons is a key event contributing to intrinsic brain inflammation [3][4][5][6][7][8][9][10][11][12]. Paracrine and autocrine activation of this signaling by the brain application of IL-1β exacerbates kainic acid-or bicuculline-induced seizures in rats and mice [5,11,13], and lowers the seizure threshold in febrile seizure models [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Paracrine and autocrine activation of this signaling by the brain application of IL-1β exacerbates kainic acid-or bicuculline-induced seizures in rats and mice [5,11,13], and lowers the seizure threshold in febrile seizure models [7,8]. Conversely, IL-1 receptor antagonist (the naturally occurring competitive antagonist of IL-1R1) mediates powerful anticonvulsant effects in rodents [6,[13][14][15] and mice over-expressing IL-1 receptor antagonist in astrocytes, or lacking IL-1R1, are intrinsically less susceptible to seizures [7,13]. These data indicate the important involvement of elevated brain IL-1β levels and the activation of IL-1R1 signaling in experimental seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental FS are induced by hyperthermia [30] which triggers processes in the brain that are similar to those evoked by fever (e.g., release of cytokines, [34,41,63,64]). For seizure generation, rat pups are placed in a glass jar and exposed to a constant stream of mildly heated air [32,73].…”
Section: Febrile Seizures and Epileptogenesismentioning
confidence: 99%